Use of Special Collections by Post Graduate Students in Selected Universities in South West Nigeria - Anyanwu, Ebataivohi Glory; Emeahara, Evelyn Nkechi; Adebayo, Oyeronke (MiddleBelt Journal of Library and Information Science, 2014)
Special collections are usually library material selected for specific purposes to meet specific needs. They are rare books and manuscripts which provide resources for the increasing needs of the research community in an academic or research institution. The study covers three universities in South West Nigeria. These universities are Lagos State University (LASU), Bowen and Covenant University. The descriptive survey and stratified random sampling method was adopted for this study. A self developed questionnaire was used to gather data from one hundred and ninety three respondents. One hundred and eighty eight copies of the questionnairewere found usable .The results of the study are shown in tables using simple percentages.The study showed that there is a high level of utilization of special collections in the selected universities. The respondents however pointed out poor bibliographic details of these special collections as a major hindrance to their quick access.